Thực hiện tính :
a) A= (x+1)(x2-3x-2)+(x+1)(x2-x+1)
b) B= (x-y)(x2+xy+y2)-(x+y)(x2+2x+y2)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1.
\(a,\left(-xy\right)\left(-2x^2y+3xy-7x\right)\)
\(=2x^3y^2-3x^2y^2+7x^2y\)
\(b,\left(\dfrac{1}{6}x^2y^2\right)\left(-0,3x^2y-0,4xy+1\right)\)
\(=-\dfrac{1}{20}x^4y^3-\dfrac{1}{15}x^3y^3+\dfrac{1}{6}x^2y^2\)
\(c,\left(x+y\right)\left(x^2+2xy+y^2\right)\)
\(=\left(x+y\right)^3\)
\(=x^3+3x^2y+3xy^2+y^3\)
\(d,\left(x-y\right)\left(x^2-2xy+y^2\right)\)
\(=\left(x-y\right)^3\)
\(=x^3-3x^2y+3xy^2-y^3\)
2.
\(a,\left(x-y\right)\left(x^2+xy+y^2\right)\)
\(=x^3-y^3\)
\(b,\left(x+y\right)\left(x^2-xy+y^2\right)\)
\(=x^3+y^3\)
\(c,\left(4x-1\right)\left(6y+1\right)-3x\left(8y+\dfrac{4}{3}\right)\)
\(=24xy+4x-6y-1-24xy-4x\)
\(=\left(24xy-24xy\right)+\left(4x-4x\right)-6y-1\)
\(=-6y-1\)
#Toru
a) \(\left(x^5+4x^3-6x^2\right):4x^2\)
\(=\left(x^5:4x^2\right)+\left(4x^3:4x^2\right)+\left(-6x^2:4x^2\right)\)
\(=\dfrac{1}{4}x^3+x-\dfrac{3}{2}\)
b) x^3 + x^2 - 12 x-2 x^3 - 2x^2 3x^2 - 12 3x^2 - 6x 6x - 12 x^2+3x+6 6x - 12 0
Vậy \(\left(x^3+x^2-12\right):\left(x-2\right)=x^2+3x+6\)
c) (-2x5 : 2x2) + (3x2 : 2x2) + (-4x^3 : 2x^2)
= \(-x^3+\dfrac{3}{2}-2x\)
d) \(\left(x^3-64\right):\left(x^2+4x+16\right)\)
\(=\left(x-4\right)\left(x^2+4x+16\right):\left(x^2+4x+16\right)\)
\(=x-4\)
(dùng hẳng đẳng thức thứ 7)
Bài 2 :
a) 3x(x - 2) - 5x(1 - x) - 8(x2 - 3)
= 3x2 - 6x - 5x + 5x2 - 8x2 + 24
= (3x2 + 5x2 - 8x2) + (-6x - 5x) + 24
= -11x + 24
b) (x - y)(x2 + xy + y2) + 2y3
= x3 - y3 + 2y3
= x3 + y3
c) (x - y)2 + (x + y)2 - 2(x - y)(x + y)
= (x - y)2 - 2(x - y)(x + y) + (x + y)2
= [(x - y) + x + y)2 = [x - y + x + y] = (2x)2 = 4x2
Bài 1 :
a]= \(\frac{1}{4}\)x3 + x - \(\frac{3}{2}\).
b] => [x3 + x2 -12 ] = [ x2 +3 ][x-2] + [-6]
c]= -x3 -2x +\(\frac{3}{2}\).
d] = [ x3 - 64 ] = [ x2 + 4x + 16][ x- 4].
\(a.2x\left(x-1\right)-3\left(x^2+4x\right)+x\left(x+2\right)\)
\(=2x^2-2x-3x^2-12x+x^2+2x\)
\(=-12x\)
\(b.\left(2x-3\right)\left(3x+5\right)-\left(x-1\right)\left(6x+2\right)+3-5x\)
\(=6x+10x-9x^2-15-6x^2-2x-6x-2+3-5x\)
\(=-15x^2+3x-14\)
\(c.\left(x-y\right)\left(x^2+xy+y^2\right)-\left(x+y\right)\left(x^2-y^2\right)\)
\(=x^3-y^3-x^3+y^3+x^2y-y^3\)
\(=y^3+x^2y\)
a: \(\dfrac{2x^4-x^3-x^2+7x-4}{x^2+x-1}\)
\(=\dfrac{2x^4+2x^3-2x^2-3x^3-3x^2+3x+4x^2+4x-4}{x^2+x-1}\)
=2x^2-3x+4
b: \(=\dfrac{y}{x\left(2x-y\right)}+\dfrac{4x}{y\left(y-2x\right)}\)
\(=\dfrac{y^2-4x^2}{xy\left(2x-y\right)}=\dfrac{-\left(2x-y\right)\left(2x+y\right)}{xy\left(2x-y\right)}=\dfrac{-2x-y}{xy}\)
c: \(=\dfrac{6\left(x+8\right)}{7\left(x-1\right)}\cdot\dfrac{\left(x-1\right)^2}{\left(x-8\right)\left(x+8\right)}=\dfrac{6\left(x-1\right)}{7\left(x-8\right)}\)
Bài 13:
a) \(501^2\)
\(=\left(500+1\right)^2\)
\(=500^2+2\cdot500\cdot1+1^2\)
\(=250000+1000+1\)
\(=251001\)
b) \(88^2+24\cdot88+12^2\)
\(=88^2+2\cdot12\cdot88+12^2\)
\(=\left(88+12\right)^2\)
\(=100^2\)
\(=10000\)
c) \(52\cdot48\)
\(=\left(50+2\right)\left(50-2\right)\)
\(=50^2-2^2\)
\(=2500-4\)
\(=2496\)
Bài 14:
a) \(P=\left(2x-1\right)\left(4x^2+2x+1\right)+\left(x+1\right)\left(x^2-x+1\right)\)
\(P=\left(2x\right)^3-1+x^3+1\)
\(P=8x^3+x^3\)
\(P=9x^3\)
b) \(Q=\left(x-y\right)\left(x^2+xy+y^2\right)-\left(x+y\right)\left(x^2-xy+y^2\right)+2y^3\)
\(Q=x^3-y^3-x^3-y^3+2y^3\)
\(Q=-2y^3+2y^3\)
\(Q=0\)
\(a,\left(x^3+5x^2-2x+1\right)\left(x-7\right)\\ =x^4-7x^3+5x^3-35x^2-2x^2+14x+x-7\\ =x^4-2x^3-37x^2+15x-7\\ b,\left(2x^2-3xy+y^2\right)\left(x+y\right)\\ =2x^3+2x^2y-3x^2y-3xy^2+xy^2+y^3\\ =2x^3-x^2y-2xy^2+y^3\\ c,\left(x-2\right)\left(x^2-5x+1\right)-x\left(x^2+11\right)\\ =x^3-5x^2+x-2x^2+10x--x^3-11x\\ =x^3-7x^2\\ d,x\left(1-3x\right)\left(4-3x\right)-\left(x-4\right)\left(3x+5\right)\\ =x\left(4-15x+9x^2\right)-\left(3x^2-7x-20\right)\\ =4x-15x^2+9x^3-3x^2+7x+20\\ =9x^3-18x^2+11x+20\)
b: (x-y)(x^2-2x+y)
\(=x^3-2x^2+xy-x^2y+2xy-y^2\)
\(=x^3-2x^2-x^2y+3xy-y^2\)
c: \(\left(x^2-y\right)\left(x+y^2\right)-\left(x-y\right)\left(x^2+xy+y^2\right)\)
\(=x^3+x^2y^2-xy-y^3-\left(x^3-y^3\right)\)
\(=x^2y^2-xy\)
d: \(3x\left(2xy-z\right)-5y\left(x^2-2\right)+3xz\)
\(=6x^2y-3xz-5x^2y+10y+3xz\)
\(=x^2y+10y\)
A = ( x + 1 )( x2 - 3x - 2 ) + ( x + 1 )( x2 - x + 1 )
= ( x + 1 )[ ( x2 - 3x - 2 ) + ( x2 - x + 1 ) ]
= ( x + 1 )( x2 - 3x - 2 + x2 - x + 1 )
= ( x + 1 )( 2x2 - 4x - 1 )
= x( 2x2 - 4x - 1 ) + 2x2 - 4x - 1
= 2x3 - 4x2 - x + 2x2 - 4x - 1
= 2x3 - 2x2 - 5x - 1
B = ( x - y )( x2 + xy + y2 ) - ( x + y )( x2 + 2x + y2 )
= x3 - y3 - ( x3 + 2x2 + xy2 + x2y + 2xy + y3 )
= x3 - y3 - x3 - 2x2 - xy2 - x2y - 2xy - y3
= -2y3 - 2x2 - xy2 - x2y - 2xy
a) \(A=\left(x+1\right)\left(x^2-3x-2\right)+\left(x+1\right)\left(x^2-x+1\right)\)
\(=x.x^2-x.3x-x.2+1.x^2-1.3x-1.2+x.x^2-x.x+x.1+1.x^2-1.x+1.1\)
\(=x^3-3x^2-2x+x^2-3x-2+x^3-x^2+x+x^2-x+1\)
\(=\left(x^3+x^3\right)+\left(-3x^2+x^2-x^2+x^2\right)+\left(-2x-3x+x-x\right)+\left(-2+1\right)\)
\(=2x^3-2x^2-5x-1\)
b) \(B=\left(x-y\right)\left(x^2+xy+y^2\right)-\left(x+y\right)\left(x^2+2x+y^2\right)\)
\(=x.x^2+x.xy+x.y^2-y.x^2-y.xy-y.y^2-x.x^2-x.2x-x.y^2+y.x^2+y.2x+y.y^2\)
\(=x^3+x^2y+xy^2-x^2y-xy^2-y^3-x^3-2x^2-xy^2+xy^2+2xy+y^3\)
\(=\left(x^3-x^3\right)+\left(x^2y-x^2y\right)+\left(xy^2-xy^2-xy^2+xy^2\right)-2x^2+2xy+\left(-y^3+y^3\right)\)
\(=-2x^2+2xy\)